Toward an Account of Intuitive Time. Issue 7 (22nd June 2022) - Lee, Ruth; Shardlow, Jack; Hoerl, Christoph; O'Connor, Patrick A.; Fernandes, Alison S.; McCormack, Teresa
Abstract: People hold intuitive theories of the physical world, such as theories of matter, energy, and motion, in the sense that they have a coherent conceptual structure supporting a network of beliefs about the domain. It is not yet clear whether people can also be said to hold a shared intuitive theory of time. Yet, philosophical debates about the metaphysical nature of time often revolve around the idea that people hold one or more "common sense" assumptions about time: that there is an objective "now"; that the past, present, and future are fundamentally different in nature; and that time passes or flows. We empirically explored the question of whether people indeed share some or all of these assumptions by asking adults to what extent they agreed with a set of brief statements about time. Across two analyses, subsets of people's beliefs about time were found consistently to covary in ways that suggested stable underlying conceptual dimensions related to aspects of the "common sense" assumptions described by philosophers. However, distinct subsets of participants showed three mutually incompatible profiles of response, the most frequent of which did not closely match all of philosophers' claims about common sense time. These exploratory studies provide a useful starting point in attempts to characterize intuitive theories of time.